2016
DOI: 10.1213/ane.0000000000001094
|View full text |Cite|
|
Sign up to set email alerts
|

Saline Flush After Rocuronium Bolus Reduces Onset Time and Prolongs Duration of Effect

Abstract: Administering a 20-mL saline flush immediately after infusion of 0.6 mg/kg rocuronium in 10 mL normal saline shortened the onset time and prolonged the recovery phase of neuromuscular blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…A study conducted by Ishigaki et al . [ 6 ] among 48 patients on the effect of 20 ml saline flush immediately after rocuronium 0.6 mg/kg administration reported that the lag time and onset time were shortened to 39 ± 11 s and 73 ± 21 s in the study group compared to 46 ± 10 s and 87 ± 22 s in the control along with prolongation of the recovery phase of neuromuscular blockade. Nitahara et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Ishigaki et al . [ 6 ] among 48 patients on the effect of 20 ml saline flush immediately after rocuronium 0.6 mg/kg administration reported that the lag time and onset time were shortened to 39 ± 11 s and 73 ± 21 s in the study group compared to 46 ± 10 s and 87 ± 22 s in the control along with prolongation of the recovery phase of neuromuscular blockade. Nitahara et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] There is limited evidence with two studies in which 20 ml saline flush immediately after administration of neuromuscular blockers followed by limb elevation which shortened the lag time and onset time in the study group compared to control group. [ 6 7 ] One of the earliest reports conclude that administration of vecuronium into a pulmonary artery significantly shortened the onset time by approximately 40 s than when compared to administration into a dorsal vein of the hand. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that anesthetic is crucial role for MEP recording and classification, so all consecutive patients underwent the same anesthesia regime. MEP baseline must be recorded after performing the rocuronium of more than 50 min [23]. The patients with different TOF might affect the MEP responses, even using total intravenous anesthesia (TIVA), thus within 100 ± 5% TOF changes were confirmed when recording MEP baseline (Fig.…”
Section: Anesthesia Managementmentioning
confidence: 99%
“…Among these are priming principle, timing principle and using high doses [5]. It has been reported in the literature that especially saline flush immediately after intravenous drug administration shortens the onset time [6,7]. Studies in the literature recommend 20 mL saline flush to be administered after adenosine, a drug with a half-life of shorter than 10 seconds and administered via a peripheral vein, to rapidly reach to the heart [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature recommend 20 mL saline flush to be administered after adenosine, a drug with a half-life of shorter than 10 seconds and administered via a peripheral vein, to rapidly reach to the heart [6]. Ishigaki et al [7] have demonstrated that 20 mL saline flush administration immediately after intravenous administration of rocuronium shortens the onset time of the drug. To the best of our knowledge, this is the first study investigating the effect of saline flush administered immediately after sugammadex on the onset time of this drug using TOF monitoring.…”
Section: Introductionmentioning
confidence: 99%